Finding the sweet spot: Li/Mn-rich cathode materials with fine-tuned core–shell particle design for high-energy lithium ion batteries. (10th January 2021) - Helbig, Jonathan; Beuse, Thomas; Siozios, Vassilios; Placke, Tobias; Winter, Martin; Schmuch, Richard
Abstract: Among current cathode materials, particular attention to Li/Mn-rich layered transition-metal oxides (LMR-NCM) emerged, due to their high energy content accompanied by concurrently low raw material cost. However, until today the step toward a successful market implementation is still impeded by substantial capacity and voltage fade phenomena upon cycling. Herein, we demonstrate a comprehensive structural and morphological approach to increase the long-term stability behavior of LMR-NCM materials within a lithium ion cell. Therefore, a recently introduced core–shell particle design concept was applied, which involves a Co-free and Mn-rich particle core and a low Co-containing shell. The resulting lower anionic redox activity of the shell is key to improve the electrochemical performance. With the aid of a Couette Taylor Flow Reactor, spherical secondary particles with high tap density and narrow particle size distribution are co-precipitated, leading to a valuable hierarchical morphology with superior electrochemical long-term behavior. Thereby, excellent initial Coulombic efficiencies of 90 – 95 % are attained. Finally, another main focus of this work concentrates on the impact of effective performance-improving shell thickness and, thus, provides further insights into the intrinsic nature of the carbonate-derived integrated LMR-NCM active materials. Graphical abstract: Image, graphical abstract